Spectroscopic and Photoluminescent Properties of Nanostructured Polyfluorenes/TiO2 Composite Films used for OLEDs - Dinh, Nguyen Nang; Chi, Le Ha; Chung Thuy, Tran Thi; Nguyen, Thien Phap (Communications in Physics, 2011)
In this work we present spectroscopic and photoluminescent properties of nanostructured polymeric composite films of nanocrystalline TiO2 and polyfuorenes (PF+nc-TiO2). The films were deposited onto glass and KBr substrates by spin-coating PF-in-toluene solution with embedding of 5-nm thick nc-TiO2 particles. The nc-TiO2 wt concentration embedded in PF was chosen as 1%, 2% and 4%. The FTIR, FTR, UV-VIS-NIR and photoluminescence characterization were carried-out to study the influence of oxide nanoparticles on the absorption spectra, molecular structures and emissive luminescence of the composites. It was shown that the presence of TiO2 nanoparticles results in improvement of charge separation of carriers generated by light excitation. Under a short wavelength excitation, in some samples a PL enhancement was observed. Under normal or long wavelength excitation, PF fluorescence quenching occurred for all the composites. Aging process of the composites was also investigated.